Il dilemma autoriale fra genre e gender: Il caso di “A Sketch of the Past” di Virginia Woolf - Gamberi, Cristina (Linguæ & - Journal of Modern Languages and Cultures, 2023)
Il dilemma autoriale fra genre e gender. Il caso di “A Sketch of the Past” di Virginia WoolfThe present article proposes a fresh reading of “A Sketch of the Past” the un-finished autobiographical piece written between 1939 and 1940 by Virginia Woolf. By retracing the genealogy of Woolf's main texts through which the reflection on female authorship in relation to the autobiographical genre is articulated, the analysis aims to highlight how its meta-reflective quality and its strong experimental component contribute to turn “A Sketch of the Past” in one of the most mature literary outcomes in life writing. By inheriting the restless dissatisfaction with the tools available, and by experimenting with strategies and practices, the piece represents an unprecedented inner self-exploration, where Woolf revisions the notion of modernist intimacy. Finally, my hypothesis is that the material conditions in which the piece was written and the history of its posthumous publication, has contributed to free Woolf from social and familial pressures and the invisible censors she was surronded.